Beyond Human Engineering Our Future Evolution - Seedhouse, Erik (Science and Fiction, 2014)
Beyond Human is an informative and accessible guide for all those interested in the developing sciences of genetic engineering, bioprinting, and human cloning. Illustrating the ideas with reference to well-known science fiction films and novels, the author provides a unique insight into and understanding of how genetic manipulation, cloning, and other novel bio-technologies will one day allow us to redesign our species. It also addresses the legitimate concerns about "playing God", while at the same time embracing the positive aspects of the scientific trajectory that will lead to our transhuman future.